The Varieties of Metaphorical Expression Values in Campaign Discourse - Pristiwati, Rahayu; Rustono, Rustono; Rahman, Fathur; Mardikantoro, Hari Bakti (The Journal of Educational Development, 2019)
This study is aimed at analyzing the varieties of metaphorical expression values found in campaign discourse. Qualitative and quantitative approaches were employed in this research. The data were excerpts of campaign discourse inPresidential and Vice Presidential National Election of Republic Indonesia in 2014. They were 320 excerpts from 322 metaphors published by Kompas, Tempo, andSuaraMerdeka newspapers within seven months, from May to September 2014. Descriptive qualitative approach was used to describe the varieties of values in metaphorical expressions. The data analysis usednormative, referential equivalent, and introspective reflective method. This analysis resulted in the following findings. The values of metaphorical expressions incampaign discourse of Presidential and Vice Presidentialnational election of Republic Indonesia in 2014 are: (1) value of mutual cooperation, (2) value of religiosity, (3) value of politeness, (4) value of simplicity, (5) value of mutual respect, (6) value of mutual assistance, (7) value of simplicity, and (8) value of deliberation.